2015
DOI: 10.18052/www.scipress.com/ilns.35.71
|View full text |Cite
|
Sign up to set email alerts
|

Comparative Efficacy of <i>Tephrosia vogelii</i> and <i>Moringa oleifera</i> against Insect Pests of Watermelon (C<i>itrullus lanatus</i> Thumb)

Abstract: Despite the fact that synthetic insecticides are fast acting, they constitute environmental hazard thereby necessitating the use of ecologically based alternative such as plant based insecticide. This experiment was conducted during the late and early planting seasons of 2011 to determine the insecticidal efficacy of Tephrosia vogelii and Moringa oleifera extracts at three tested concentrations (5, 10 and 20% v/v) against insect pests of watermelon. The experiment was set up in a randomized complete block desi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The efficacy of moringa homemade botanical insecticide has been primarily assessed in storage applications, except in 1 study by Alao and Adebayo (2015) in which aqueous extracts of moringa controlled dipteran and coleopteran pests in the field (Tables 1 and 2…”
Section: Moringa (Moringa Oleifera)mentioning
confidence: 99%
See 1 more Smart Citation
“…The efficacy of moringa homemade botanical insecticide has been primarily assessed in storage applications, except in 1 study by Alao and Adebayo (2015) in which aqueous extracts of moringa controlled dipteran and coleopteran pests in the field (Tables 1 and 2…”
Section: Moringa (Moringa Oleifera)mentioning
confidence: 99%
“…In field applications, tephrosia aqueous extracts have been used successfully to control coleopteran pests (Alao and Adebayo 2015;Mkenda et al 2015a;Tembo et al 2018), dipteran pests (Alao and Adebayo 2015), hemipteran pest (Mkenda et al 2015a;Tembo et al 2018), and lepidopteran pests (Olaitan and Abiodun 2011) ( Table 1). In comparison with positive controls, the efficacy was often similar or inferior (3 instances each), but was superior in 1 instance (Table 2).…”
Section: Tephrosia (Tephrosia Vogelii)mentioning
confidence: 99%
“…Also, Ojiako et al, (2013) had found that M. oleifera seed extracts reduced the number of Megalurothrips sjostedti and A crassivora. Also, M. oleifera extracts had 62 % reduction of Phyllotreta cruciferae (Alao and Adebayo, 2015). Using plant extracts as bio-pesticides offering the farmers many unique benefits, it is usually are inherently less harmful than conventional the pesticides (John and Jimmy, 2015).…”
Section: Insecticidal Activity Extract Of Moringa Oleifera and Thiamementioning
confidence: 99%
“…In Kenya, where both cutaneous and visceral leishmaniases are andemic and are conditions. The study was carried out using only the preemerginal stages because female adults feed on blood and both sexes suitable plant for carbohydrates [22]. It was envisaged that targeting the pre-emerginal stages can be achieved through introduction of the crude dried T. vogelii into the termite mound and animal burrow breeding and resting sites of the sand fl ies.…”
Section: Introductionmentioning
confidence: 99%